Medical dressing with tissue adhesion and antifouling properties and preparation method thereof
By coupling the hydrophilic hydrogel adhesion layer and the hydrophobic silicone anti-fouling barrier layer, the adhesion between layers is enhanced by inorganic nanoparticles, and an adhesion gel dressing with multiple barrier functions is developed, which solves the problems of low tissue adhesion and insufficient anti-fouling performance in complex wound repairs, and achieves efficient wound repair effects.
Patent Information
- Application Number
- CN202411121453.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-15
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-08-15
AI Technical Summary
In the repair of complex wounds, existing medical dressings have problems such as low tissue adhesion, insufficient antifouling performance, and susceptibility to erosion in the gastric environment, which is difficult to meet the needs of clinical complex wounds.
By coupling the hydrophilic hydrogel adhesion layer and the hydrophobic silicone anti-fouling barrier layer, using inorganic nanoparticles to provide more bonding sites, an adhesion gel dressing with multiple barrier functions is developed to achieve both tissue adhesion and anti-fouling properties.
The dressing exhibits excellent wet adhesion ability on complex wound surfaces, can effectively isolate H+ penetration, prevent microbial adhesion and provide solid lubrication, significantly improving the effect of wound repair.
Smart Images

Figure CN119838040A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of medical dressings, and in particular relates to a medical dressing having both tissue adhesion and antifouling properties and a preparation method thereof. Background Art
[0002] A wound is an injury that causes the skin, tissues and mucous membranes to lose continuity. Since wounds are usually directly exposed to a complex environment, they are susceptible to bacterial infection, which in turn causes a persistent inflammatory response at the site of infection, resulting in delayed wound healing and, in some special cases, even serious complications.
[0003] Medical dressings are usually used to cover wounds and create a moist environment for wound healing. Among them, traditional dressings such as cotton wool, cotton wool, and gauze have been widely used in clinical practice because of their economical cost to ensure wound cleanliness and prevent bacterial infection. However, fibers easily adhere to granulation tissue, causing pain and secondary damage when removing the dressing. The new gel dressing can maintain the ideal temperature and humidity of the wound and stimulate wound healing. In addition, hydrogels have both the high biocompatibility of natural polymers and the elastic mechanical properties of synthetic polymers, making them more suitable for various wounds and therefore widely used.
[0004] Some self-gel adhesive gel powders, such as polyethyleneimine and polyacrylic acid powders, can absorb interfacial water within 2 seconds and form physically cross-linked hydrogels in situ due to the strong physical interactions between the polymers. In addition, the physically cross-linked polymers can diffuse into the substrate polymer network to enhance wet adhesion.
[0005] However, due to the interference of excessive interfacial water and limited interaction between the adhesive and the tissue, this gel powder still cannot meet the repair requirements of some complex wounds in clinical practice. For example, for patients with gastric cancer treated by endoscopic submucosal dissection, artificial ulcers will be left after surgery. Although the powder can be delivered to the wound surface under endoscopy, in the special environment of the stomach, the hydrogel cannot isolate the penetration of digestive juices and gastric acid from causing erosion and stimulation to the wound surface, as well as infection by various bacteria and enzymes, and the adhesive cannot establish long-lasting and effective protection on the wound surface. Providing a reliable repair barrier for the ulcer surface through this gel strategy remains a challenge and an urgent clinical need.
[0006] Cross-linked polydimethylsiloxane and other polymer materials have been widely used in artificial skin, medical cosmetic surgery and other fields due to their good flexibility, strong corrosion resistance and good biocompatibility. However, the formation of the three-dimensional cross-linked network of cross-linked polydimethylsiloxane usually depends on the hydrosilylation reaction between polydimethylsiloxane containing two vinyl end groups and a multifunctional cross-linking agent. Therefore, cross-linked polydimethylsiloxane itself does not have dynamic covalent bonds and bioadhesion, and cannot be directly used for wound protection.
[0007] In view of this, the present application provides a medical dressing having both tissue adhesion and anti-fouling properties and a preparation method thereof to solve the above-mentioned technical problems. Summary of the invention
[0008] In response to the above-mentioned problems in the prior art, the present application proposes a medical dressing having both tissue adhesion and anti-fouling properties and a preparation method thereof. The method utilizes inorganic nanoparticles to provide more bonding sites, couples the hydrophilic hydrogel adhesion layer and the hydrophobic silicone anti-fouling barrier layer, and develops a multi-barrier functional adhesion gel based on differential wettability and lubrication design, which has application prospects in tissue damage repair under a variety of complex environments.
[0009] A medical dressing with both tissue adhesion and antifouling properties comprises an antifouling barrier layer and a tissue adhesion layer, wherein the antifouling barrier layer and the tissue adhesion layer are coupled via inorganic nanoparticles.
[0010] As a preferred solution, the antifouling barrier layer is a hydrophobic organosilicon antifouling barrier layer, wherein the hydrophobic organosilicon antifouling barrier layer is made by curing a lubricating liquid and a siloxane liquid in one step.
[0011] As a preferred solution, the tissue adhesion layer is a hydrophilic hydrogel adhesion layer, and the hydrophilic hydrogel adhesion layer is formed by PEI / PAA-NHS hydrogel powder absorbing water and gelling in situ on the wound surface.
[0012] As a preferred solution, the inorganic nanoparticles are a thin layer of nano-silicon dioxide powder evenly sprayed on the surface of the bioadhesive material. The nano-silicon dioxide powder can provide more bonding sites and strengthen the interlayer adhesion.
[0013] A method for preparing a medical dressing having both tissue adhesion and antifouling properties, comprising the following steps:
[0014] S1. Synthesis of N-hydroxysuccinimide grafted polyacrylate. Under ice bath conditions, a certain proportion of polyacrylic acid, N,N-dicyclohexylcarbodiimide and N-hydroxysuccinimide were fully dissolved in a 1:1 mixed solution of dichloromethane and N,N-dimethylformamide. The N,N-dicyclohexylcarbodiimide pre-solution was added dropwise to the polyacrylic acid solution. After 5 minutes, the N-hydroxysuccinimide pre-solution was added dropwise to the reaction solution in the same manner. After stirring for 1 hour under ice bath conditions, stirring was continued at 22°C for 12 hours. During the reaction, N,N-dicyclohexylcarbodiimide was converted into N,N-dicyclohexylurea which was insoluble in organic reagents. After filtering, the filtrate was dried at low temperature. The obtained product was washed with ammonia water and dichloromethane and dried in a vacuum.
[0015] S2. Preparation of polyethyleneimine / polyacrylate hydrogel powder: 10 wt% polyethyleneimine solution and 10 wt% polyacrylate solution were mixed in a certain ratio while stirring, and the obtained polyethyleneimine / polyacrylate hydrogel solution was poured into liquid nitrogen for freezing, grinding, and freeze-drying, and the prepared polyethyleneimine / polyacrylate hydrogel powder was stored in a low-temperature dry environment.
[0016] S3, formation of adhesive gel layer. Spray the prepared polyethyleneimine / polyacrylate hydrogel powder on the wound surface, and the dry powder quickly absorbs water to form an in-situ gel, which can fully adapt to the complex wound morphology.
[0017] S4. Strengthening the interlayer adhesion. Evenly spray a thin layer of nano-silicon dioxide powder on the surface of the bioadhesive material to provide more bonding sites and strengthen the interlayer adhesion;
[0018] S5. Preparation of prepolymer liquid of organic silicon barrier layer. At low temperature, take a certain proportion of siloxane liquid, lubricating liquid and silane coupling agent, mix them evenly, and centrifuge at 1500r / min for 1 minute to degas;
[0019] S6. Formation of a multifunctional barrier. The prepared silicone barrier layer prepolymer solution is injected onto the hydrogel layer and waited for 10 minutes at room temperature for it to completely solidify, thereby forming a medical dressing having both tissue adhesion and anti-fouling properties.
[0020] As a preferred solution, the degree of polymerization of the polyacrylic acid in step S1 is 200k-800kDa.
[0021] As a preferred solution, the molar ratio of N,N-dicyclohexylcarbodiimide as a coupling mediator in step S1 to N-hydroxysuccinimide is maintained at 1:1; the mass ratio of N-hydroxysuccinimide to polyacrylic acid is between 3:1 and 1:1.
[0022] As a preferred solution, the degree of polymerization of the polyethyleneimine in step S2 is 70 kDa.
[0023] As a preferred solution, the ratio of the 10% polyethyleneimine solution to the 10% polyacrylate solution in step S2 is 1:3.
[0024] As a preferred solution, the particle size of the nano silicon dioxide powder in step S4 is 20 to 5000 nm.
[0025] As a preferred solution, the silicone liquid in step S5 is preferably Ecoflex TM 00-35AB, polymethylsiloxane, polyethylsiloxane, epoxysiloxane, fluorocarbon polymer.
[0026] As a preferred solution, the lubricating liquid in step S5 is preferably hydrophobic silicone oil or fluorinated oil.
[0027] As a preferred solution, the silane coupling agent in step S5 is preferably vinyltrimethoxysilane.
[0028] As a preferred solution, in step S5, the mass fraction of the siloxane liquid is 30% to 50%, the mass fraction of the lubricating fluid is 50% to 70%, and the mass fraction of the silane coupling agent is 0.1 to 0.2%.
[0029] As a preferred solution, the viscosity of the dimethyl silicone oil in step S5 is 1000-10000 cst.
[0030] The above technical features can be combined in a suitable manner or replaced by equivalent technical features as long as the purpose of the present invention can be achieved.
[0031] Compared with the prior art, the beneficial effects of the present invention are:
[0032] Existing adhesive hydrogel dressings are used for complex wound repair. For example, they show limited clinical efficacy in the gastric environment, which is manifested in the following aspects: 1) The adhesion between the hydrogel and tissue interface is low, and the pulling force caused by gastric peristalsis, contraction, and relaxation can easily cause the dressing to detach; 2) The dressing lacks H+ intervention measures. The H+ in the gastric cavity can penetrate the dressing and erode the wound due to the concentration difference, causing the adhesive interface to become unstable and fall off.
[0033] Based on the needs of wound management, the present invention couples functions and develops a multi-barrier adhesive gel dressing by regulating the wettability of the interface. The adhesive gel includes a hydrophilic gel adhesion layer and a hydrophobic silicone barrier layer. First, the hydrogel adhesion layer is prepared by dry powder water-absorbing in-situ gelation, which has excellent wet adhesion ability and can adapt well to the complex morphology of the wound surface in the stomach. Subsequently, the prepolymer liquid of the silicone barrier layer is injected onto the hydrogel layer. During the in-situ gelation process, the hydrogel and silicone are stably bonded through silicon-oxygen chemical bonds. The dressing can establish strong adhesion with wet tissue, and the interface changes from hydrophilic to hydrophobic, realizing multiple barrier functions of isolating H+ penetration, preventing microbial attachment and solid lubrication. The in-situ construction facilitates application in various scenarios. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] The present invention will be described in more detail below based on embodiments and with reference to the accompanying drawings, wherein:
[0035] Figure 1 The test results of the adhesion strength between Examples 1-3 of the present invention and pig skin tissue are shown;
[0036] Figure 2 The FTIR infrared spectrum test diagrams of Examples 1-3 of the present invention are shown;
[0037] Figure 3 The statistical graph of the number of E. coli colonies on the plate after culturing in E. coli suspension for 6 hours and 24 hours in Examples 1, 4-7 of the present invention is shown;
[0038] Figure 4 The statistical graphs of the surface adhesion protein areas of Examples 1, 4-7 of the present invention after being cultured in a fluorescently labeled bovine serum albumin PBS solution for 6 hours and 24 hours are shown;
[0039] Figure 5 A diagram showing the structure of the medical dressing of the present invention is shown. DETAILED DESCRIPTION
[0040] The present invention will be further described below in conjunction with the accompanying drawings.
[0041] The present invention provides a medical dressing having both tissue adhesion and antifouling properties and a preparation method thereof. Figure 5As shown, the medical dressing with both tissue adhesion and antifouling properties includes a hydrophilic hydrogel adhesion layer and a hydrophobic silicone antifouling barrier layer, wherein the barrier layer is made by curing a lubricating liquid and a silicone liquid in one step. The present invention also provides a method for preparing a medical dressing with both tissue adhesion and antifouling properties, comprising pre-modifying PAA with NHS, mixing the modified PAA-NHS with PEI to prepare a PEI / PAA-NHS hydrogel powder with strong adhesion, and then coupling the adhesion layer and the barrier layer with inorganic nanoparticles. The medical dressing with both tissue adhesion and antifouling properties prepared by the present invention has excellent wet adhesion ability, and also realizes multiple barrier functions of isolating H+ penetration, preventing microbial adhesion and solid lubrication, which can effectively promote wound healing in various situations.
[0042] Example 1
[0043] 10 g of a 10 wt% polyethyleneimine aqueous solution (Mv, ca. 70,000) and 20 g of a 10 wt% polyacrylic acid aqueous solution (Mv, ca. 240,000) were mixed with stirring, the mixture was poured into liquid nitrogen for freezing, ground, and freeze-dried in a freeze dryer for 48 hours to obtain a polyacrylic acid / polyethyleneimine hydrogel powder.
[0044] Example 2
[0045] Under ice bath conditions, 2g of polyacrylic acid, 4.13g of N,N-dicyclohexylcarbodiimide and 2.30g of N-hydroxysuccinimide were fully dissolved in a 1:1 mixed solution of dichloromethane and N,N-dimethylformamide. The N,N-dicyclohexylcarbodiimide pre-solution was added dropwise to the polyacrylic acid solution. After 5 minutes, the N-hydroxysuccinimide pre-solution was added dropwise to the reaction solution in the same manner. After stirring for 1 hour under ice bath conditions, stirring was continued at 22°C for 12 hours. During the reaction, N,N-dicyclohexylcarbodiimide was converted into N,N-dicyclohexylurea which was insoluble in organic reagents. After filtering, the filtrate was dried at low temperature. The obtained product was washed with ammonia water and dichloromethane, and then dried in a vacuum to obtain a modified polyacrylate powder, which was dissolved in water to prepare a 20g polyacrylate solution.
[0046] 10 g of 10 wt% polyethyleneimine solution and 20 g of the above-prepared polyacrylate solution were mixed while stirring, and the mixture was poured into liquid nitrogen for freezing, grinding, and freeze-drying in a freeze dryer for 48 hours to obtain polyethyleneimine / polyacrylate hydrogel powder, which was stored in a low-temperature dry environment.
[0047] Example 3
[0048] Under ice bath conditions, 2g of polyacrylic acid, 8.26g of N,N-dicyclohexylcarbodiimide and 4.60g of N-hydroxysuccinimide were fully dissolved in a 1:1 mixed solution of dichloromethane and N,N-dimethylformamide. The N,N-dicyclohexylcarbodiimide pre-solution was added dropwise to the polyacrylic acid solution. After 5 minutes, the N-hydroxysuccinimide pre-solution was added dropwise to the reaction solution in the same manner. After stirring for 1 hour under ice bath conditions, stirring was continued at 22°C for 12 hours. During the reaction, N,N-dicyclohexylcarbodiimide was converted into N,N-dicyclohexylurea which was insoluble in organic reagents. After filtering, the filtrate was dried at low temperature. The obtained product was washed with ammonia water and dichloromethane, and then dried in a vacuum to obtain a modified polyacrylate powder, which was dissolved in water to prepare a 20g polyacrylate solution.
[0049] 10 g of 10 wt% polyethyleneimine solution and 20 g of the above-prepared polyacrylate solution were mixed while stirring, and the mixture was poured into liquid nitrogen for freezing, grinding, and freeze-drying in a freeze dryer for 48 hours to obtain polyethyleneimine / polyacrylate hydrogel powder, which was stored in a low-temperature dry environment.
[0050] Example 4
[0051] At low temperature, take 5g of Ecoflex TM 00-35A, 5g Ecoflex TM 00-35B and 0.01 g of vinyltrimethoxysilane were mixed evenly, centrifuged at 1500 r / min for 1 minute to degas, injected between two glass plates, and waited for 10 minutes at room temperature for polymerization.
[0052] Example 5
[0053] At low temperature, take 2g of Ecoflex TM 00-35A, 2g Ecoflex TM 00-35B, 6g of 1000cst dimethyl silicone oil and 0.01g of vinyltrimethoxysilane were mixed evenly, centrifuged at 1500r / min for 1 minute to degas, injected between two glass plates, and waited for 10 minutes at room temperature for polymerization.
[0054] Experimental Example 6
[0055] At low temperature, take 2g of Ecoflex TM 00-35A, 2g Ecoflex TM00-35B, 6g of 10000cst dimethyl silicone oil and 0.01g of vinyltrimethoxysilane were mixed evenly, centrifuged at 1500r / min for 1 minute to degas, injected between two glass plates, and waited for 10 minutes at room temperature for polymerization.
[0056] Experimental Example 7
[0057] At low temperature, take 2g of Ecoflex TM 00-35A, 2g Ecoflex TM 00-35B, 6g of 500000cst dimethyl silicone oil and 0.01g of vinyltrimethoxysilane were mixed evenly, centrifuged at 1500r / min for 1 minute to degas, injected between two glass plates, and waited for 10 minutes at room temperature for polymerization.
[0058] Take the samples prepared in the above experimental example and conduct the following experiment:
[0059] 1. The hydrogel powders prepared in Experimental Examples 1 to 3 were tested for bioadhesion by lap shear test. 40 mg of hydrogel powder was sandwiched between two pig skin tissues with a bonding area of 1 cm x 1 cm. The samples were then incubated at 37°C for 5 min and pressurized (applied 8 kPa pressure). The maximum tensile stress was then tested using a universal tensile machine.
[0060] Figure 1 It is the adhesion strength test result of each sample. It can be seen from the figure that the adhesion strength of the hydrogel adhesion powder modified by N-hydroxysuccinimide has been significantly improved, and it increases with the increase of N-hydroxysuccinimide content.
[0061] 2. The hydrogel powders prepared in Experimental Examples 1 to 3 were tested by FTIR infrared spectroscopy. The results are as follows: Figure 2 As shown. Figure 2 It is known that, through modification with N-hydroxysuccinimide, the carboxyl groups of polyacrylic acid originally formed amide bonds with free amino groups to form polymerized N-hydroxysuccinimide esters, which is also the reason why the adhesion of the hydrogel powder after modification is improved.
[0062] 3. The samples prepared in Experimental Examples 1, 4 to 7 were subjected to in vitro antibacterial experiments. The samples were cut into 0.5 cm × 0.5 cm pieces, and all samples were incubated in E. coli suspension (1 × 107 cells ml-1) at 37 ° C for different time periods (6 h and 24 h). After incubation, the bacteria loosely attached to the surface of the sample were washed off, and then the bacteria attached to the surface were ultrasonically eluted and collected by centrifugation. The collected bacterial suspension was further diluted and spread on a Luria broth (LB) agar plate and cultured at 37 ° C for 24 h.
[0063] Figure 3It is the antibacterial test result of each sample against Escherichia coli. It can be seen from the figure that the organic silicon barrier layer (experimental examples 4 to 7) prepared by the present invention has a good antibacterial effect.
[0064] 4. The samples prepared in Experimental Examples 1, 4 to 7 were subjected to in vitro anti-protein adhesion experiments. The selected samples were incubated at 37°C for different time periods (6h and 24h) in a suspension of fluorescently labeled bovine serum albumin (BSA-FITC) (10μl BSA-FITC was added to 20ml PBS buffer). The loosely attached proteins on the sample surface were washed off, and then the surface fluorescence was observed by confocal microscopy to calculate the percentage of the adherent protein area.
[0065] Figure 4 It is the anti-protein adhesion test result of each sample. It can be seen from the figure that the organic silicon barrier layer (Examples 4 to 7) prepared by the present invention has a good anti-protein adhesion effect.
[0066] 5. Animal experiments. The digestive system of pigs is similar to that of humans, and their special environment is most suitable for experimental research on complex wound repair. Therefore, the inventors created two ulcer surfaces with a diameter of 0.8 cm in the stomach of living pigs, and treated the wounds with either no treatment or a medical dressing with both tissue adhesion and antifouling properties.
[0067] Experiments show that the medical dressing having both tissue adhesion and anti-fouling properties of the present invention has a significant effect on promoting the repair of tissue damage in complex situations.
[0068] Although the present invention is described herein with reference to specific embodiments, it should be understood that these embodiments are merely examples of the principles and applications of the present invention. It should therefore be understood that many modifications may be made to the exemplary embodiments and that other arrangements may be devised without departing from the spirit and scope of the present invention as defined by the appended claims. It should be understood that the various dependent claims and features described herein may be combined in a manner different from that described in the original claims. It should also be understood that features described in conjunction with individual embodiments may be used in other described embodiments.
Claims
1. A medical dressing having both tissue adhesion and antifouling properties, characterized in that: It comprises an antifouling barrier layer and a tissue adhesion layer, wherein the antifouling barrier layer and the tissue adhesion layer are coupled via inorganic nanoparticles.
2. The medical dressing having both tissue adhesion and antifouling properties according to claim 1, characterized in that: The antifouling barrier layer is a hydrophobic organic silicone antifouling barrier layer, wherein the hydrophobic organic silicone antifouling barrier layer is prepared by curing a lubricating liquid and a silicone liquid in a one-step process.
3. The medical dressing having both tissue adhesion and antifouling properties according to claim 1, characterized in that: The tissue adhesion layer is a hydrophilic hydrogel adhesion layer, and the hydrophilic hydrogel adhesion layer is formed by PEI / PAA-NHS hydrogel powder absorbing water and gelling in situ on the wound surface.
4. The medical dressing having both tissue adhesion and antifouling properties according to claim 1, characterized in that: The inorganic nanoparticles are a thin layer of nano-silicon dioxide powder evenly sprayed on the surface of the bioadhesive material. The nano-silicon dioxide powder can provide more bonding sites and strengthen the interlayer adhesion.
5. A method for preparing a medical dressing having both tissue adhesion and antifouling properties, characterized in that: The preparation method comprises the following steps: S1. Under ice bath conditions, polyacrylic acid, N,N-dicyclohexylcarbodiimide and N-hydroxysuccinimide are dissolved in a mixed solution of dichloromethane and N,N-dimethylformamide respectively; a pre-solution of N,N-dicyclohexylcarbodiimide is added to the polyacrylic acid solution, and the pre-solution of N-hydroxysuccinimide is later added dropwise to the reaction solution in the same manner; during the reaction, N,N-dicyclohexylcarbodiimide is converted into N,N-dicyclohexylurea which is insoluble in organic reagents, which is filtered and dried; the obtained product is washed with ammonia water and dichloromethane and then dried; S2, mixing 10wt% polyethyleneimine solution and 10wt% polyacrylate solution while stirring, pouring the obtained polyethyleneimine / polyacrylate hydrogel solution into liquid nitrogen for freezing, grinding, and freeze-drying, and storing the prepared polyethyleneimine / polyacrylate hydrogel powder in a low-temperature dry environment; S3, spray the prepared polyethyleneimine / polyacrylate hydrogel powder on the wound surface, the dry powder quickly absorbs water to form a hydrogel, which can fully adapt to the complex wound morphology; S4, evenly spray a thin layer of nano-silicon dioxide powder on the surface of the tissue adhesion layer to provide more bonding sites and strengthen the interlayer adhesion; S5, mixing the siloxane liquid, the lubricating liquid and the silane coupling agent uniformly and degassing to obtain a prepolymer liquid of the organosilicon barrier layer; S6. Inject the prepolymer liquid of the silicone barrier layer onto the hydrogel layer and wait for it to completely solidify at room temperature, thereby forming a medical dressing having both tissue adhesion and anti-fouling properties.
6. The method for preparing a medical dressing having both tissue adhesion and antifouling properties according to claim 5, characterized in that: The polymerization degree of the polyacrylic acid is 200k-800kDa.
7. The method for preparing a medical dressing having both tissue adhesion and antifouling properties according to claim 5, characterized in that: The molar ratio of N,N-dicyclohexylcarbodiimide as a coupling mediator to N-hydroxysuccinimide is maintained at 1:1; the mass ratio of N-hydroxysuccinimide to polyacrylic acid is between 3:1 and 1:
1.
8. The method for preparing a medical dressing having both tissue adhesion and antifouling properties according to claim 5, characterized in that: The ratio of 10% polyethyleneimine solution to 10% polyacrylate solution is between 1:3 and 1:
1.
9. The method for preparing a medical dressing having both tissue adhesion and antifouling properties according to claim 5, characterized in that: The silicone liquid is EcoflexTM00-35AB, polymethylsiloxane, polyethylsiloxane, epoxysiloxane, and fluorocarbon polymer.
10. The method for preparing a medical dressing having both tissue adhesion and antifouling properties according to claim 5, characterized in that: The mass fraction of the siloxane liquid is 30% to 50%, the mass fraction of the lubricating fluid is 50% to 70%, and the mass fraction of the silane coupling agent is 0.1% to 0.2%.
Citation Information
Patent Citations
Multi-layered wound dressing containing an hydrocolloid and activated carbon
CN103889468A
Dentoid polymer, method for decorating iron oxide nanoparticles by utilizing dentoid polymer and product prepared through method
CN108314786A
Double-sided amphiphilic composite medical dressing and preparation method thereof
CN117752844A
Wound dressing with ultraviolet barrier layer and producing method for the same
KR1020110118439A
Polyethyleneglycol-polylactic acid-polyethylenimine cationic copolymer, preparation method thereof, and drug delivery composition comprising the copolymer
KR1020140019214A